(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article examines the role of information technology in ensuring the financial security of the organisation. Financial security allows an organisation to provide financial protection against internal and external threats, which contributes to effective functioning and maintaining competitive advantage. Theft of company and customer funds causes serious damage to the organisation’s activities and negates all efforts to develop financial security. We will look at the key aspects of using digital technologies to ensure the stability of businesses, their benefits and challenges, as well as examples of successful implementation of digital strategies in practice. The most important role in ensuring the financial security of modern organisations is played by the use of information technologies. The authors of the article consider the possibility of using modern information technologies to ensure financial security of enterprises. To ensure and develop financial security in organisations it is proposed to use innovative distributed registry technology.